IMPLEMENTASI TATA KELOLA DANA DESA DALAM PENINGKATAN TARAF KESEJAHTERAAN DESA - Gus Kiki Setiawan; Lintje Anna Marpaung (Gapenas Publisher, 2021)
The village is the unity of the legal community with the original order based on the privileged right of origin. The typical principles of village government are diversity, participation, autonomy, democracy and community empowerment. This research aims to find out the implementation of village fund governance in improving village welfare levels in Pekon Gunung Ratu, Bandar Negeri Suoh District, West Lampung Regency which is currently in accordance with the concerns of legislation but not yet maximal in its implementation. The problem is the lack of human resources, the pekon apparatus lack of understanding of village fund management rules, lack of understanding of the main tasks and functions of each office of the pekon apparatus, lack of aspirations and role of the community and the communication of the community and the lack of communication between the community and the government. The research method used is qualitative method. This means that the results of this study are described in the form of explanations and descriptions in sentences, so that it is easy to interpret and understand, then drawn conclusions that are general based on facts specific to the research subject. Qualitative research methods are research procedures that produce descriptive data in the form of writing and oral writing of a person and observable behavior. Where the results obtained are data obtained from the field obtained from the collection of primary data which include interviews, observations, literature studies, archives / documents, and writing literature related to research